2009
DOI: 10.1038/ijo.2008.280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a lifestyle intervention on change in cardiorespiratory fitness in adults with type 2 diabetes: results from the Look AHEAD Study

Abstract: ObjectiveTo examine the effect of an intensive lifestyle weight loss intervention (ILI) compared to diabetes support and education (DSE) on changes in fitness and physical activity in the Look AHEAD trial.DesignRandomized clinical trial to compare a lifestyle intervention for weight loss with a diabetes support and education condition in individuals with type 2 diabetes.SubjectsData from 4,376 overweight or obese adults with type 2 diabetes (age = 58.7±6.8 years, BMI = 35.8±5.8 kg/m2) who completed one-year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 17 publications
4
129
1
Order By: Relevance
“…The majority of patients seem to enjoy the program and feel that it helped them lost weight and manage their disease ( Figure 3F). Data from twenty longitudinal cohort studies and six large-scale diabetes prevention intervention trials in adults with impaired glucose tolerance or at high risk of cardiovascular disease unanimously reflected the beneficial effect of moderate physical activity (approximately 150 minutes per week) in reducing the risk of developing the T2DM by nearly 20-30% [23][24][25][26]. Substantial amelioration of risk (40-60%) is achieved in pre-diabetic patients however with rigorous lifestyle intervention counseling for physical activity, nutrition, and weight loss [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients seem to enjoy the program and feel that it helped them lost weight and manage their disease ( Figure 3F). Data from twenty longitudinal cohort studies and six large-scale diabetes prevention intervention trials in adults with impaired glucose tolerance or at high risk of cardiovascular disease unanimously reflected the beneficial effect of moderate physical activity (approximately 150 minutes per week) in reducing the risk of developing the T2DM by nearly 20-30% [23][24][25][26]. Substantial amelioration of risk (40-60%) is achieved in pre-diabetic patients however with rigorous lifestyle intervention counseling for physical activity, nutrition, and weight loss [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Copenhagen Type 2 Diabetes Rehabilitation Project [30]-a randomized control trial of a small population of patients with T2DM undergoing a rehabilitation program consisting of empowerment-based education, supervised exercise and dietary intervention -found similar reductions at 1-year in weight (2.2 vs 1.6 kg), waist circumference (2.0 vs 1.6 cm), HbA1c (0.2 vs 0.4%), sBP (6 vs 3 mmHg) and dBP (4 vs 3 mmg) between the rehabilitation group versus the individual outpatient primary care group, suggesting both models of care are of similar efficacy [31]. Larger seminal trials, however, such as the Look AHEAD trial [32], clearly showed early superiority of the intensive lifestyle intervention arm versus the conventional treatment arm, with the former group having lost >5% in more than 50% of patients despite a lack of clear cardiovascular benefit at 9.6-yrs of follow-up [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Waist Circumference Weight Loss and Selfempowermentmentioning
confidence: 99%
“…The Look AHEAD study showed greater improvements in cardiorespiratory fitness for men compared with women at both the 1-and 4-year followup, even with adjustment for baseline fitness levels. 243,261 In contrast, both women and men with T2DM appeared to have similar improvements in fitness in response to exercise training interventions in the Diabetes Aerobic and Resistance Exercise trial 253 and in a meta-analysis of physical activity interventions among people with T2DM.…”
mentioning
confidence: 99%
“…Combined approaches described above are effective in reducing insulin resistance [82], and decreasing CVD, heart failure, stroke, cancer, diabetes, and all-cause mortality [83][84][85]. However, because of poor compliance, unwillingness to accept obesity as a disease, and associated social stigma [19], the overall effectiveness of therapies for weight loss and metabolic syndrome is imperfect.…”
Section: Overall Management Of Obesity and T2dmentioning
confidence: 99%